My life as a zucchini [videorecording (Blu-Ray)] - Sciamma, Céline, 1980-; Sedaris, Amy (Shout! Factory, 2025)
After losing his mother, a young boy is sent to a foster home with other orphans his age where he begins to learn the meaning of trust and true love.